TRANSLATION IN LIBEL CASES: REPUTATIONS AT STAKE! - Scott, Juliette; O'Shea, John Anthony (Comparative Legilinguistics, 2022)
Abstract: In this paper we examine translation arising in court cases involving reputational damage. A diachronic and tightly focused cross-jurisdictional selection of examples from case law is used to highlight the range of ways in which translation can be employed, blamed, or relied upon by the parties and by the courts, and we glimpse how translations can be a source of libel, a defence against libel, or a gateway to libellous material, how crucial translation can be in protecting or damaging reputations, and how significantly it can affect a case’s outcome. We apply Engberg’s lens for communication in legal contexts, distinguishing micro, meso and macro occurrences of translation at publisher/business/individual, judicial, and State levels. Recurring translation-related topics either mooted by courts or arising in our analysis are then outlined, including: competing translations; translation techniques; translator identification; online translation; how the acceptance of jurisdiction may be influenced by translation requirements; and how judges approach decision-making when foreign language documents and translation are involved.